EVALUATION OF THE PARAMETERS OF CHARQUI MEAT AND JERKED BEEF MARKETED IN SOUTH OF BRAZIL - Coelho, Alexandre Rodrigo; Garcia Coró, Fábio Augusto; Fontana, Herrison Yoshiki Yocida (IJRDO-Journal of Applied Science, 2017)
Charqui and jerked beef, typical foods from certain regions of the Brazil. These products are interestingdue to the added value to less noble meat, to meat from older animals and of doubtful sensory quality forfresh consumption. Physicochemical and microbiological analyses were performed on four differenttrademark of charqui and on three of jerked beef. The physicochemical tests were ascertained by moisturecontents, ash, water activity (Aw) and pH. Regarding the microbiological testing, there was the estimatedcount of total coliforms and thermotolerants (MPN/g) and the enumeration of coagulase positiveStaphylococcus. The objective of this study is to evaluate the quality of Charqui and jerked beef marked inthe Southern Region of Brazil. The physical-chemical data for the samples analyzed were in accordancewith the standards expected in current laws.